Development of a Storytelling Video Self-Help Intervention Based on Acceptance and Commitment Therapy for Major Depression: Open Trial Results. Issue 1 (January 2019) - Gaudiano, Brandon A.; Davis, Carter H.; Miller, Ivan W.; Uebelacker, Lisa A.
This study involved the initial development and testing of a video self-help intervention called LifeStories, which features real patients describing their use of coping strategies for depression based on Acceptance and Commitment Therapy. We conducted a baseline-controlled open trial (AB design) of 11 individuals diagnosed with major depressive disorder. Participants reported high levels of satisfaction and transportation (i.e., engagement) after watching LifeStories . No significant changes were observed during the 4-week baseline period in terms of interviewer-rated depression severity (primary outcome), but a significant and large effect size improvement was observed at Week 8 postintervention. The majority of participants (54.5%) showed a reliable and clinically significant posttreatment response. Significant improvements also were observed during the intervention period only for self-reported depressive symptoms and aspects of mindfulness (nonreactivity). Qualitative data analysis of participant interviews identified additional areas for improvement and refinement. Future testing in a randomized trial is warranted based on these encouraging results.